2021
DOI: 10.3390/microorganisms9122596
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Histoplasmosis in a Cohort of People with HIV: From Estimations to Reality

Abstract: Among people with HIV, histoplasmosis represents an important cause of mortality. Previous studies provided estimates of the disease incidence. Here, we compared those estimates with the results obtained from a screening program implemented in Guatemala, which included histoplasmosis detection for people with HIV. To compare the results of this program with previous estimations, a literature search was performed and reports concerning histoplasmosis incidence were analyzed. The screening program enrolled 6366 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…Despite that, none of these studies previously done were part of governmental programmes, making all these initiatives unviable in the long term, highlighting the importance of the inclusion of fungal diseases in public health programmes, as well as its mandatory reporting, which will be essential for strengthening programmes and burden estimation of these diseases. 8 , 9 , 10 , 11 , 12 , 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…Despite that, none of these studies previously done were part of governmental programmes, making all these initiatives unviable in the long term, highlighting the importance of the inclusion of fungal diseases in public health programmes, as well as its mandatory reporting, which will be essential for strengthening programmes and burden estimation of these diseases. 8 , 9 , 10 , 11 , 12 , 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…This study also showed a trend to less mortality when a positive antigen detection test precedes a diagnosis by conventional methods (14.3% versus 26.9%), which corroborates the observation that in North America, where antigen detection is widely available, mortality rates of DH are significantly lower (around 10%) [ 8 , 14 ]. In Guatemala, a similar trend towards reduced mortality in PLWHA when Histoplasma antigen was made available was observed, which was probably linked to an earlier and quicker diagnosis [ 10 ].…”
mentioning
confidence: 89%
“…As they are commercially available, a proficiency quality control program is easy to set up to validate the quality of the laboratory results. These tests have proven to diagnose more cases when compared to conventional methods as well as having an impact on patients’ survival [ 8 10 ]. The performance of Histoplasma antigen testing in the non-HIV population deserves further investigation.…”
mentioning
confidence: 99%
“… 44 The same group showed that implementation of a screening program in people with HIV irrespective of clinical suspicion or CD4 count led to a doubling of diagnoses of histoplasmosis compared with a previous estimate and identification of a 33.8% rate of co-infection with cryptococcosis. 45 Mpoza and colleagues reported that CrAg positivity was 4% in those with HIV VLs > 5000 copies/mL, irrespective of CD4 counts. 15 Although it was beyond the scope of this study to examine screening in individuals with higher CD4 counts, a higher CD4 count cutoff and/or additional factors may be needed to guide screening in ART-experienced people living with HIV.…”
Section: Discussionmentioning
confidence: 99%